2016
DOI: 10.22359/cswhi_7_2_01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spa treatment and speleotherapy in the treatment of chronic obstructive pulmonary disease – a pilot study

Abstract: Abstract:Objective: The aim of our research was to determine the effect of Speleotherapy on the quality of life, anxiety and depression in patients with COPD. Design: Pilot study. Participants: The 128 patients with CPOD participated in the study (average age 64.05), examined during a spa treatment in a sanatoriums in the High Tatras. The experimental group (29 patients) completed spa treatment and Speleotherapy in the Belianska Cave. The control group (99 patients) completed a spa treatment without Speleother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Other evidence suggests that longer-term exposure to caves may benefit mental and physical health. For example, a 19-day intervention revealed that speleotherapy might be conducive to reducing anxiety and increasing walking ability (Kendrová et al, 2016). Another 12-week study reported that speleotherapy helped athletes enhance their athletic performance, such as increasing boxers' punch speed, jump, reaction, VO2max (how efficiently someone uses oxygen during exercise), and balance (Söyler et al, 2021).…”
Section: Cavesmentioning
confidence: 99%
“…Other evidence suggests that longer-term exposure to caves may benefit mental and physical health. For example, a 19-day intervention revealed that speleotherapy might be conducive to reducing anxiety and increasing walking ability (Kendrová et al, 2016). Another 12-week study reported that speleotherapy helped athletes enhance their athletic performance, such as increasing boxers' punch speed, jump, reaction, VO2max (how efficiently someone uses oxygen during exercise), and balance (Söyler et al, 2021).…”
Section: Cavesmentioning
confidence: 99%
“…There are also clues that longer-term exposure to caves may benefit mental and physical health. For example, a 19-day intervention revealed that speleotherapy might be conducive to reducing anxiety and increasing walking ability (Kendrová et al, 2016). Another 12-week study reported that speleotherapy helped athletes enhance their athletic performance, such as increasing boxers' punch speed, jump, reaction, VO2max (how efficiently someone uses oxygen during exercise), and balance (Söyler et al, 2021).…”
Section: Cavesmentioning
confidence: 99%
“…Programs carried out in locations with low pollution levels, such as pollution-free underground salt chambers or caves, yield substantial health improvements. This environment thus complements and enhances the effects of respiratory muscle training in pulmonary rehabilitation [13][14][15]. The specific microclimate is characterized by an absence of pollutants and allergens, a high concentration of salt aerosol, high relative humidity, stable temperature, elevated atmospheric pressure, ionization, and deprivation of external stimuli.…”
Section: Introductionmentioning
confidence: 95%